Investigation of Demodex and superficial flora in patients with Rosacea - Aytaç, Özlem; Gürok, Neşe Göçer; Şenol, Feray Ferda; Toraman, Zülal Aşçi; Öztürk, Savaş (Refik Saydam National Public Health Agency (RSNPHA), 2023)
Objective: In our study, it was aimed to investigate the presence of Demodex spp. and bacterial population in rosacea patients and to contribute to the treatment process of the disease. Methods: In the study, 90 patients who applied to Elazig Fethi Sekin City Hospital Dermatology policlinic were diagnosed with rosacea were included. Samples were taken from rosacea patients with active lesions by standard superficial skin biopsy (SSSB). Aerobic and anaerobic cultures were performed bacteriologically on the samples taken from the simultaneous lesion. Microorganisms grown in culture were identified by Matrix assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS, Bruker, Germany) mass spectrometry. Results: A total of 90 patients, 74 (82.2%) females and 16 (17.8%) males, were included in the study. Demodex positivity was observed in 63 of them (70%). Of the patients, 65 (72.2%) were ETR and 25 (27.8%) were PPR patients. The growth rate of Staphylococcus epidermidis (S. epidermidis) was found to be significantly higher in ETR patients (29.2%) than in PPR patients (8%). Staphylococcus aureus (S. aureus) growth rate was found to be significantly lower in ETR patients (30.8%) than in PPR patients (56%) (p<0.05). However, there was no significant difference between the growth status of B. cereus (p=1,000), B. pumilus (p=1,000), E. coli (p=0,435) and S. pneumonia (p=0,557) bacteria according to rosacea clinical subtypes of the patients. B. cereus growth in Demodex positive ETR patients was found to be significantly higher than in PPR patients (p<0.05). Conclusion: According to the data we obtained in our study, we think that Bacillus species (such as B. cereus, B. pumilus), which were not emphasized much in previous studies, and S. aureus may contribute to the development of clinical subtypes of the disease. As a result; Considering this situation in the treatment of Demodex, it will be beneficial to plan the clinical symptoms of the disease. © 2023, Turk Hijyen ve Deneysel Biyoloji Dergisi. All Rights Reserved.
Rozasealı hastalarda Demodex ve yüzeyel bakteri florasının araştırılması
Keywords: Demodex; Rozasea; superficial bacterial flora